Seeing Realities: How Language Acquisition Shapes Our View of of the World - Basuki, Irawan Santoso Suryo (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2025)
Language is one of the tools humans use to express ideas, thoughts, images, and understandings about the world. However, the position of language between thoughts and the reality of the world observed through our five senses is not yet clear. The question is whether language influences the way humans view the reality around them, or if, on the other hand, reality influences humans' thoughts about the world. This paper seeks to explain the issue of language's position between thoughts and the world by comparing the concepts of the Principle of Linguistic Relativity proposed by Benjamin Lee Whorf and Language Games introduced by Ludwig Wittgenstein. Literature studies were conducted by examining Wittgenstein's Philosophical Investigations and works that influenced Whorf's Language, Thought, and Reality. This paper concludes that the position of language is not between thoughts and the reality of the world, but rather encompasses and bridges both. The key to understanding this relationship lies in the two-way interaction that language regulates. This reciprocal mechanism is often overlooked in language learning and neglecting the fact that language can shape each individual’s perspective of the world. Realities are seen in many ways, as many as languages used to perceive them.